2016
DOI: 10.3390/s16071143
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of Sensor Nodes with Hybrid Measurements in Wireless Sensor Networks

Abstract: Localisation in wireless networks faces challenges such as high levels of signal attenuation and unknown path-loss exponents, especially in urban environments. In response to these challenges, this paper proposes solutions to localisation problems in noisy environments. A new observation model for localisation of static nodes is developed based on hybrid measurements, namely angle of arrival and received signal strength data. An approach for localisation of sensor nodes is proposed as a weighted linear least s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…is the run number andx i is the estimate of the true target location, x oi , during the i th run. We compare the performance of our algorithm to that of the LS method in [17], WLLS algorithm in [23], and LS_WLS and WLS method in [22]. We also evaluate the performance of the real ECWLS algorithm, which replaces the estimated noise with the true noise variances in the ECWLS algorithm.…”
Section: Performance Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…is the run number andx i is the estimate of the true target location, x oi , during the i th run. We compare the performance of our algorithm to that of the LS method in [17], WLLS algorithm in [23], and LS_WLS and WLS method in [22]. We also evaluate the performance of the real ECWLS algorithm, which replaces the estimated noise with the true noise variances in the ECWLS algorithm.…”
Section: Performance Resultsmentioning
confidence: 99%
“…The error covariance matrix for LS is simple to compute (see Appendix A, which corrects the missing terms in the correlation matrix presented in [24]). The weighted LS algorithm using the covariance matrix is termed the WLLS algorithm [23]. Although the LS method is intuitive and simple, the performance comparisons in [24] and in Section 6 in this paper showed that the WLS method outperforms the LS method, while the WLS method is, in turn, outperformed by the WLLS algorithm due to the introduction of error covariance weights.…”
Section: Related Workmentioning
confidence: 88%
See 2 more Smart Citations
“…Note that this is in sharp contrast to the existing approaches for joint RSS and AOA localization (both non-cooperative [10]- [14] and cooperative [17]- [19]), where the measurement errors of angle observations were considered as Gaussian random variables. The von Mises distribution is a circular analogue of the Gaussian one, and since we are dealing here with directional data, it comes more natural to consider this distribution rather than the Gaussian one [20], [21].…”
Section: Problem Formulationmentioning
confidence: 99%